2009
DOI: 10.29046/tmf.011.1.009
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Babesiosis Complicated by Hepatic and Renal Failure

Abstract: A 67-year-old male with a past medical history of chronic kidney insufficiency, splenectomy, and recurrent babesiosis infection was transferred to with jaundice and abdominal pain.The patient initially presented to an outside hospital (OSH) with generalized weakness, chills, and gastrointestinal symptoms and was found to have Babesia on peripheral blood smears. The patient received seven days of azithromycin and atovaquone, followed by three days of clindamycin and quinine sulfate. The patient was discharged h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…These analyses confirmed the powerful influence of the invasion on the structure of the renal tubules. Krawitz et al 28 confirmed the occurrence of complications from the excretory system in the course of human babesiosis.…”
Section: Discussionmentioning
confidence: 92%
“…These analyses confirmed the powerful influence of the invasion on the structure of the renal tubules. Krawitz et al 28 confirmed the occurrence of complications from the excretory system in the course of human babesiosis.…”
Section: Discussionmentioning
confidence: 92%
“…A case of a man with Babesia merozoites was described in the literature. The spleen parenchyma was soft, brittle, and not enlarged, and the histopathological analysis of the spleen after splenectomy showed changes in the red pulp, in which there was an increase in the number of plasma cells, histiocytes, immunoblasts, and lymphocytes with features of hyperplasia [26].…”
Section: Discussionmentioning
confidence: 99%
“…This results in liver, kidney, or spleen failure among the most common complications of acute babesiosis 15,16,17,18,19,20 . Krawitz et al 21 described a case of a 67-year-old man with renal and hepatic failure in the course of babesiosis. The patient's age and lack of a spleen were predisposing factors for complications in the course of infection.…”
Section: Discussionmentioning
confidence: 99%